FILLERS IN ELON MUSK'S SPONTANEOUS SPEECHES - Tabitha, Ratya Khelin; Bram, Barli (JOURNAL OF LANGUAGE, 2024)
Fillers are expressions to bridge the gap between thoughts when there is a pause in communication. This paper aims to discover the types and functions of fillers used by Elon Musk in his spontaneous speeches. The study was a descriptive qualitative study that applied discourse analysis. The data were Elon Musk's spontaneous speeches containing fillers collected from the transcripts of two interview videos. Two research questions were formulated, namely, first, what the types of fillers in Elon Musk's spontaneous speeches were and second, what the fillers functioned in the speeches. To answer the questions, the researchers used Rose's (1998) theory on the types of fillers, which incorporated a similar concept on the types and functions retrieved from Baalen (2001). The results showed 932 lexicalized and 430 unlexicalized fillers, and five functions in 13 kinds of fillers. The findings imply that it is vital to introduce the types and functions of fillers to increase learners' awareness of fillers when they hesitate in a foreign language, which is the essence of speaking.